2022
DOI: 10.15252/embr.202154371
|View full text |Cite
|
Sign up to set email alerts
|

Phytochrome B enhances seed germination tolerance to high temperature by reducing S‐nitrosylation of HFR1

Abstract: Light and ambient high temperature (HT) have opposite effects on seed germination. Light induces seed germination through activating the photoreceptor phytochrome B (phyB), resulting in the stabilization of the transcription factor HFR1, which in turn sequesters the suppressor PIF1. HT suppresses seed germination and triggers protein S‐nitrosylation. Here, we find that HT suppresses seed germination by inducing the S‐nitrosylation of HFR1 at C164, resulting in its degradation, the release of PIF1, and the acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 71 publications
(135 reference statements)
1
13
0
1
Order By: Relevance
“…Thus 80 Snitrosylated proteins were identified, including glyceraldehyde 3-phosphate dehydrogenase, indicating that S-nitrosylation of this enzyme may accelerate cell death and seed deterioration during aging; similar results were obtained for Arabidopsis seeds [231]. It has been recently reported that elevated temperature (32 °C) inhibits Arabidopsis seed germination and triggers protein S-nitrosylation [232]. Under this temperature, the bHLH transcription factor LONG HYPOCOTYL IN FAR-RED1 (HFR1) is S-nitrosylated at Cyt164, resulting in its degradation and breakdown PIF1-HFR1 heterodimer to release PHYTOCHROME INTERACTING FACTOR 1 (PIF1) activity.…”
Section: Protein S-nitrosylationsupporting
confidence: 61%
See 1 more Smart Citation
“…Thus 80 Snitrosylated proteins were identified, including glyceraldehyde 3-phosphate dehydrogenase, indicating that S-nitrosylation of this enzyme may accelerate cell death and seed deterioration during aging; similar results were obtained for Arabidopsis seeds [231]. It has been recently reported that elevated temperature (32 °C) inhibits Arabidopsis seed germination and triggers protein S-nitrosylation [232]. Under this temperature, the bHLH transcription factor LONG HYPOCOTYL IN FAR-RED1 (HFR1) is S-nitrosylated at Cyt164, resulting in its degradation and breakdown PIF1-HFR1 heterodimer to release PHYTOCHROME INTERACTING FACTOR 1 (PIF1) activity.…”
Section: Protein S-nitrosylationsupporting
confidence: 61%
“…Ainsi, 80 protéines Snitrosylées ont été identifiées, dont la glycéraldéhyde 3-phosphate déshydrogénase, indiquant que la Snitrosylation de cette enzyme peut accélérer la mort cellulaire et la détérioration des graines au cours du vieillissement ; des résultats similaires ont été obtenus pour les graines d'Arabidopsis [231]. Il a été récemment signalé qu'une température élevée (32 °C) inhibe la germination des graines d'Arabidopsis et déclenche la S-nitrosylation des protéines [232]. Sous cette température, le facteur de transcription bHLH LONG HYPOCOTYL IN FAR-RED1 (HFR1) est Snitrosylé à Cyt164, entraînant sa dégradation et la rupture de l'hétérodimère PIF1-HFR1 pour libérer l'activité du PHYTOCHROME INTERACTING FAC-TOR 1 (PIF1).…”
Section: S-nitrosylation Des Protéinesunclassified
“…Light and high temperature have opposite effects on seed germination, while light induces, heat suppresses seed germination. Recently, S-nitrosation of LONG HYPOCOTYL IN FAR-RED1 (HFR1) offered a mechanistic link between light-and heat-controlled seed germination [86]. Light stabilizes HFR1 that forms a heterodimeric complex with PIF1 and inhibits its DNA binding activity, thereby promoting seed germination under light.…”
Section: Hfr1mentioning
confidence: 99%
“…Light stabilizes HFR1 that forms a heterodimeric complex with PIF1 and inhibits its DNA binding activity, thereby promoting seed germination under light. However, high temperature induces S-nitrosation of HFR1 Cys164, resulting in its degradation and release of PIF1 that activates expression of the CCCH-type zinc finger protein SOMNUS which can alter GA and ABA metabolism and finally suppress seed germination [86].…”
Section: Hfr1mentioning
confidence: 99%
“…NO mechanisms during plant acclimation to HS include activation of cellular responses through the S -nitrosylation of the trihelix TF GT-1, which promotes its binding to HEAT SHOCK TRANSCRIPTION FACTOR A2 ( HsfA2 ) promoter ( He et al., 2022 ). During germination, Cys S -nitrosylation has been described as an important PTM, where high temperature and the photoreceptor phytochrome B (phyB) modulate antagonistically LONG HYPOCOTYL IN FAR-RED (HFR1)-SNO to coordinate seed thermotolerance ( Ying et al., 2022 ).…”
Section: High and Low-temperature Stressmentioning
confidence: 99%